Rehabilitación oral "prostodoncia" (1999)
Prostodóncia/Amalgamas/Resinas de fotocurado/Incrustaciones/Coronas completas/Prótesis parcial fija/Prótesis total/Prótesis parcial removible/Implantes/Articulación tempero mandibular